Processing Method Altered Mouse Intestinal Morphology and Microbial Composition by Affecting Digestion of Meat Proteins - Xie, Yunting; Wang, Chong; Zhao, Di; Zhou, Guanghong; Li, Chunbao (Frontiers in Microbiology, 2020)
Our previous study showed that the intake of meat proteins dynamically affected fecal microbial composition. However, the digestion of processed meat proteins in vivo and its relationship with gut microbiota and host remain unclear. In this study, we collected cecal contents and intestinal tissue from the mice fed with casein, soybean protein (SP), and four processed pork proteins for 8 months, and analyzed the amino acid (AA) files, cecum microbial composition and metabolites and intestinal morphology. Dry-cured pork protein and stewed pork protein (SPP) groups had significantly higher total AAs contents in gut contents than the other groups, but the content of SPP group was relatively lower in the serum. The microbial composition of the processed meat protein groups differed from the casein or SP group, which is consistent with changes in AA composition. Emulsion sausage protein and SP diets upregulated the microbial amino acid metabolism, energy metabolism, signaling molecules and interaction, translation, digestive system function but downregulated the microbial membrane transport, signal transduction and cell motility function than the casein diet. The SPP diets increased concentrations of acetate, propionate, butyrate and isovalerate by specific gut microbes, but it decreased the relative abundance of Akkermansia. Moreover, the mice fed SP diet had relatively lower crypt depth, higher villus height and V/C ratio in duodenum, with the longer small intestines and the heavier cecum than other diets. These results suggested that processing methods altered bioavailability of meat proteins, which affected the intestinal morphology and the cecum microbial composition and function.